Critical Counter-Narrative as Transformative Methodology for Educational Equity. Issue 1 (March 2020) - Miller, Richard; Liu, Katrina; Ball, Arnetha F.
Counter-narrative has recently emerged in education research as a promising tool to stimulate educational equity in our increasingly diverse schools and communities. Grounded in critical race theory and approaches to discourse study including narrative inquiry, life history, and autoethnography, counter-narratives have found a home in multicultural education, culturally sensitive pedagogy, and other approaches to teaching for diversity. This chapter provides a systematic literature review that explores the place of counter-narratives in educational pedagogy and research. Based on our thematic analysis, we argue that the potential of counter-narratives in both pedagogy and research has been limited due to the lack of a unified methodology that can result in transformative action for educational equity. The chapter concludes by proposing critical counter-narrative as a transformative methodology that includes three key components: (1) critical race theory as a model of inquiry, (2) critical reflection and generativity as a model of praxis that unifies the use of counter-narratives for both research and pedagogy, and (3) transformative action for the fundamental goal of educational equity for people of color.